Transcriptional Regulation of Carotenoid Biosynthesis in Plants: So Many Regulators, So Little Consensus - Stanley, Lauren; Yuan, Yao-Wu (Frontiers in Plant Science, 2019)
In plants, the carotenoid biosynthesis pathway (CBP) is essential for the production of photosynthetic and protective pigments, plant hormones, and visual/olfactory attractants for animal pollinators and seed dispersers. The regulation of carotenoid biosynthesis at the transcriptional level is vitally important for all of these functions, and has been the subject of intensive research. Many putative transcriptional regulators, both direct and indirect, have been identified through conventional mutant analysis, transcriptome profiling, yeast-one-hybrid screening, and candidate gene approaches. Despite this progress, our understanding of the transcriptional regulation of carotenoid biosynthesis remains fragmented and incomplete. Frequently, a stimulus or regulator is known, but the mechanism by which it affects transcription has not been elucidated. In other cases, mechanisms have been proposed (such as direct binding of a CBP gene promoter by a transcription factor), but function was tested only in vitro or in heterologous systems, making it unclear whether these proteins actually play a role in carotenoid regulation in their endogenous environments. Even in cases where the mechanism is relatively well understood, regulators are often studied in isolation, either in a single plant species or outside the context of other known regulators. This presents a conundrum: Why so many candidate regulators but so little consensus? Here we summarize current knowledge on transcriptional regulation of the CBP, lay out the challenges contributing to this conundrum, identify remaining knowledge gaps, and suggest future research directions to address these challenges and knowledge gaps.